Media Massa dan Kreativitas Berbahasa - Elly Delfia (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2012)
Mass Media is a means of reaching a large audience using different kinds of communication methodes which promates the creativity of language. Various forms of language creativity grow and develop on television programs and social networking. Language creativity successfully blurs the line between the truth and lies between the real and cybernetic world. Nowndays, the popular form of language creativity on the television programs is the uses of adulation and ambigiuous expressions. As a consequence, these expressions are a clear-cut portrait of Indonesian mentality and Intelection.